Inhibition of Barium Sulfat Crystal Formation in a Batch Method Crystallizer in the Presence of Cu and Zn - Karaman, Novel; Giritama Wibowo, Hendi; Aqil, Ubaidillah; Jamari, Jamari; Bayuseno, A.P.; Suprianti, Lilik (Publisher Cv. Inara, 2023)
Deposits of barium sulfate are a common issue in the oil and gas industry. The presence of these crystals impacts oil and gas production, causing technical problems such as inhibiting flow rate, increasing pressure in the pipe, and causing the pipe to break and be damaged. The results of this study show the formation of barium sulfate (BaSO4) crystals with the batch crystallizer method at 300 °C under the influence of the stirring rotation speed (0 rpm, 120 rpm, 240 rpm, 360 rpm, 480 rpm) and the additive concentration (0 ppm, 5 ppm, 10 ppm, 15 ppm, 2atm). In this study, the BaSO4 crystallization experiment was performed in a glass beaker using a magnetic stirrer with a stirring rotation speed to react BaCL2 and Na2SO4. The results demonstrated that adding zinc chloride (ZnCl2) and copper (ii) chloride (CuCl2) additives reduced the mass of crystals formed. The amount of barium sulfate scale that forms can be affected by the rotational speed of the stirrer. According to SEM analysis, the crystal morphology of BaSO4 was orthorhombic, indicating that this crystal shape was typical of barite crystals. While XRD analysis confirmed the formation of barium sulfate (barite) crystals, it also demonstrated that the crystals formed were solid barite crystals.